Analisis Sistem Rekrutmen dan Seleksi Tenaga Kesehatan di Rumah Sakit Permata Depok Tahun 2020 - Wikan Kawedhar, (2021)
Health workers are one of the health human resources that are very strategic in their existence. To get health workers according to the number of needs, quality and competence, the hospital organizes recruitment and selection activities. This study discusses the recruitment and selection system for health personnel at Permata Depok Hospital in 2020 using a systems approach consisting of input, process, and output. This research is a qualitative study using in-depth interviews, observation and document review methods. The informants of this study consisted of HRD managers, HRD recruitment staff, nursing managers, medical service managers, as well as new employees of health analysts and nurses. The results obtained are the input from the recruitment and selection that has been going well, but there is a change in the sequence of selection procedures due to pandemic conditions so that it is not in accordance with the specified standard operating procedures, the psychological test room is inadequate and applicants who take part in the recruitment are still not according to user expectations. The process of recruitment and selection originates from internal and external sources using open methods but there are obstacles that are not sufficient for the applicant's internet network so that the implementation of online interviews is not optimal and one of the informants is not given a psychological test. The output of this recruitment and selection of health workers is in accordance with the qualifications but there are still underperforming health workers.